Pengaruh Pelatihan dan Knowledge Sharing Terhadap Kinerja Guru Dimediasi Oleh Motivasi Kerja (Studi Pada Lembaga Pendidikan Yayasan Setia Medan). - Tamba, Rustina; Nahrisah, Ezzah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted at the Setia Medan Foundation Educational Institution with the aim of the research to determine the effect of training and knowledge sharing on teacher performance mediated by work motivation. The population was employees and teachers who worked at the Setia Medan Foundation educational institution, random sampling using the Slovin formula so that the number of research samples was 74 respondents. The source of research data is primary and data collection techniques are by survey. Data analysis techniques use path analysis, classical assumption tests and hypothesis tests.Based on the results of the research conducted, it shows that partially training and knowledge sharing have a positive and significant effect on work motivation and employee performance. Work motivation mediates the effect between training on employee performance, but work motivation does not mediate the effect between knowledge sharing on employee performance. Training, knowledge sharing and work motivation simultaneously have a significant effect on employee performance at the Yayasan Setia Medan Educational Institution.